DEVELOPMENT OF A MULTIPLEXED CONFOCAL FLUORESCENCE LIFETIME IMAGING MICROSCOPE FOR SCREENING APPLICATIONS - Hirmiz, Nehad (My University, 2019)
Protein-protein interactions are important for biological processes. Therefore, many small molecules target a specific protein or interaction in the cell to have biological consequence. While we can measure some protein-protein interactions in a test tube, many proteins cannot be purified making it difficult to properly test that a drug is “on target”. An alternative is to measure these interactions in live cells. We express the proteins of interest fused to fluorophores allowing the use of fluorescence techniques. Förster Resonance Energy Transfer (FRET) provides a molecular level ruler to measure the distance, within a few nanometers, between two proteins. FRET indicates binding. The gold standard for measuring FRET in live cells is by quantifying changes in fluorescence lifetime using Fluorescence lifetime imaging microscopy (FLIM). The change in fluorescence lifetime is inversely proportional to the ratio of bound to non-bound proteins. Tradition FLIM-FRET microscopy is too slow for screening applications. Our aim was to develop a highly multiplexed confocal system for rapid FLIM-FRET acquisition. We present the development of multiple prototypes for confocal multiplexing. In this work, our final design includes 32×32 multiplexed excitation points which scan the sample using refractive window scanners. We coupled this excitation scheme to a 64×32 time-gated single-photon avalanche photodiode (SPAD) sparse array detector. This multiplexed setup allows the use of the sparse array with high frame rate and sub-nanosecond time-gating to achieve high throughput FLIM acquisition. Using our multiplexed FLIM prototype we measured Bcl-2 family protein-protein interactions in live cells (310×310 μm FOV) with two-channel confocal FLIM in 1.5 s. Protein binding affinities were estimated by measuring the changes in FRET as a function of acceptor to donor ratio. The resulting speed of this system meets requirements for implementation in screening applications.
Keywords: Fluorescence Microscopy; Confocal Microsopy; Fluorescence Lifetime; Rapid Imaging; Drug Screening